HIF-1α as a Mediator of Insulin Resistance, T2DM, and Its Complications: Potential Links With Obstructive Sleep Apnea - Gabryelska, Agata; Karuga, Filip Franciszek; Szmyd, Bartosz; Białasiewicz, Piotr (Frontiers in Physiology, 2020)
Obstructive sleep apnea syndrome (OSA) is described as an independent risk factor for the onset and progression of type 2 diabetes (T2DM), as well as for insulin resistance (IR). The mechanisms underlying these processes remain still unclear. One of the proposed molecular mechanism is based on the oxygen-sensitive α-subunit of hypoxia-inducible factor 1 (HIF-1 α) – a key regulator of oxygen metabolism. The concept that stabilization of HIF-1α may influence T2DM and IR is supported by cell and animal models experiments. Cell culture studies revealed that both glucose uptake and glycolysis are regulated by HIF-1α. Furthermore, animal models indicated that increased fasting glucose may be caused by a single night with intermittent hypoxia. Moreover, in these models hypoxia time was correlated with IR. Mice models revealed that inhibition of HIF-1α protein may down-regulate fasting blood glucose and plasma insulin level. Administration of superoxide dismutase mimetic resulted in inhibition of HIF-1α protein, catecholamines, and chronic intermittent hypoxia-induced hypertension in mice model. The hypothesis that hypoxia is an independent risk factor for IR is strengthened by an experimentally confirmed improvement of insulin sensitivity among OSA patients treated with continuous positive airway pressure. Furthermore, recent studies suggest that HIF-1α protein concentration is increased in individuals with OSA. In this literature review, we summarize the current knowledge about HIF-1α in OSA in relation to the possible pathways in which they contribute to metabolic disorders.